The Regional Market for the Development of Outsourcing Services - BAGUZOVA, Larisa V.; SUSLOVA, Julia J.; ANANEVA, Nadezhda V.; KUIMOV, Vasiliy V.; VEREMEENKO, Olga S. (Journal of Advanced Research in Law and Economics, 2017)
Despite its relative maturity – more than 15 years of development – the outsourcing sector remains understudied. Companies that provide outsourcing services are few and far between and only several companies engage in this practice on a large scale. In Russia, the pioneers of outsourcing of business processes (and many of its other types) were foreign companies. The purpose of this study is to describe the modern Russian market of outsourcing services. The study offers a method for calculating the effectiveness of outsourcing based on the comparison of costs method. The tools used in the study included SWOT analysis and the outsourcing matrix. One of the features of the study is the calculation of the economic efficiency of transferring works and services to an external executor. This technology can be used by trading companies. Special values stems from the fact that the study gives examples of actual activities of Astur LLC trading company related to the outsourcing of IT services. The results describe the advantages of and threats associated with outsourcing services. The study shows, under which conditions the outsourcing will allow the company to gain maximum benefit therefrom and how these services affect the company’s organizational activity.